Dinamika Populasi Arthropoda pada Pertanaman Kubis (Brassica oleracea L.) di Desa Kerinjing Kota Pagar Alam - Nunilahwati, Haperidah; Purwanti, Yani; Nisfuriah, Laili; Dali, Dali; Kalasari, Rastuti; Zairani, Fitri Yetty; Hasani, Burlian; Rompas, Joni Philep; Ferdianto, Rizky (Seminar Nasional Lahan Suboptimal, 2024)
Nunilahwati, H., Purwanti, Y., Nisfuriah, L., Dali., Kalasari, R., Zairani, FY., Hasani, B., Rompas, JP & Ferdianto, R. (2024). Arthropoda population dynamics in cabbage plants (Brassica oleracea L.) in Kerinjing Village, Pagar Alam City. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 512–522).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Arthropods can affect the economic and ecological success of agroecosystems in cabbage plantations. The study aimed to obtain data on the dynamics and types of arthropods in cabbage plantations. The study was conducted in cabbage plantations in Kerinjing Village, Pagaralam City from June 2024 to July 2024. The method used to determine the types and populations of arthropods was by setting traps on the soil surface and insect nets (sweep nets) for arthropods in the plant canopy. Data were analyzed using analysis of variance (ANOVA) and further Least Significant Difference (LSD) tests at a significance level of 5%. The results of the study found six orders of arthropods, namely Araneida, Coleoptera, Dermaptera, Hymenoptera, Lepidoptera, and Orthoptera. The population of arthropods in each order was found to fluctuate. The highest population in the Dermaptera order was 6.79 individuals, and the lowest in the Araneida order was 0.78 individuals, while in the Coleoptera, Hymenoptera, Lepidoptera, and Orthoptera orders were 0.83, 0.92, 2.46, and 0.93, respectively. Data on the dynamics of diverse arthropod populations can be the basis for determining the timing and methods of environmentally friendly and sustainable pest population control in cabbage plantations.